Linearity study on detection and quantification limits for the determination of avermectins using linear regression - Ismail, Rafidah; Lee, Hai Yen; Mahyudin, Nor Ainy; Abu Bakar, Fatimah (National Laboratories of Foods and Drugs, 2014)
In this study, linear relationships between response and concentration were used to estimate the detection limit (DL) and quantification limit (QL) for five avermectins: emamectin, abamectin, doramectin, moxidectin, and ivermectin. Estimation of DL and QL was based on the standard deviation of residual and y-intercept of the regression line at low concentrations of avermectins, using the dispersive solid-phase extraction procedure. Avermectin extracts were analyzed using liquid chromatography tandem mass spectrometry. Based on the regression slope, DL and QL were higher at concentrations of 0.3–0.4 μg/kg and 1 μg/kg, respectively, for all avermectin compounds. Linearity assessment was performed by linear regression, which incorporated a regression model, outlier rejection, and evaluation of the assumption with a significant test. For all avermectins, there is a significant correlation between response and concentration in the range 1–15 μg/kg, and the y-intercept passes through origin (zero).